Effects of Volatile Asset Priceson Balance of Payments and International Investment Position - Committeri, Marco (IMF Working Papers; Working Paper ;, 2000)
This paper aims at clarifying, with the help of a simple formal model and numerical examples, several aspects of the relationship between international investment position (IIP) and balance of payments (BOP) statistics. Exact and approximated relations are compared to analyze the estimation accuracy of the most popular data model used to reconcile BOP transaction statistics with IIP and external debt stock statistics, and discuss (a) how such accuracy is affected by volatile asset prices and transactions and (b) how net errors and omissions are related to the model in question. Numerical examples based on equity prices and exchange rates actually observed in the 1990s suggest that the bias might have been especially large for estimates based on less detailed financial information. Serious consideration should be therefore given by national compilers to make use of more detailed financial information in compiling BOP and IIP statistics.